2016
DOI: 10.1007/s10973-015-5202-z
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and anelastic relaxations accompanying relaxor ferroelectric behaviour of Ba6GaNb9O30 tetragonal tungsten bronze from resonant ultrasound spectroscopy

Abstract: Tetragonal tungsten bronze (TTB) structures offer some promise as lead-free ferroelectrics and have an advantage of great flexibility in terms of accessible composition ranges due to the number of crystallographic sites available for chemical substitution. The ferroic properties of interest are coupled with strain, which will be important in the context of stability, switching dynamics and thin film properties. Coupling of strain with the ferroelectric order parameter gives rise to changes in elastic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…In the last few years, traditionally, niobates with tetragonal tungsten bronze structure (TTB) as KSr 2 Nb 5 O 15 (KSN) have proved to be of technological interest principally due to the high anisotropy of the crystalline structure and ferroelectric properties with great potential for applications such as sensor devices, actuators, memories, filters and capacitors (wireless communication) [11,12]. Nickelzinc ferrites are typical polycation oxides exhibiting an inverse spinel structure with a complex cation distribution in the crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, traditionally, niobates with tetragonal tungsten bronze structure (TTB) as KSr 2 Nb 5 O 15 (KSN) have proved to be of technological interest principally due to the high anisotropy of the crystalline structure and ferroelectric properties with great potential for applications such as sensor devices, actuators, memories, filters and capacitors (wireless communication) [11,12]. Nickelzinc ferrites are typical polycation oxides exhibiting an inverse spinel structure with a complex cation distribution in the crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…The observed softening is mainly related to the shear modulus. 14,30 The symmetry change from Pm3m/Fm3 to R3 at T trans implies an improper ferroelastic anomaly, which corresponds to a step change in the elastic constants through linear-quadratic coupling (eP 2 and eQ 2 ). 6,14 Instead, a continuous softening is observed which reflects the change of the microstructure with temperature.…”
Section: Please Cite This Article As Doi: 101063/15116753mentioning
confidence: 99%
“…However, during the last few years, the research was mostly directed to the synthesis and characterisation of novel TTB ferroelectric and ferroelectric-related materials [8][9][10][11][12][13][14][15][16][17][21][22][23][24][25][26], with Sr 5 Nb 10 O 30 -Ba 5 Nb 10 O 30 system (SBN) [27] and Ba 6 FeNb 9 O 30 (BFNO) [28][29][30][31] as the main starting point. These ceramic materials exhibit actually relaxor ferroelectric/dielectric phenomena [6,12,[32][33][34][35][36][37]; in the BFNO-related materials, it was shown that due to the variable oxidation state of Fe (Fe 3+ /Fe 2+ ) appear oxygen vacancy gradients, and both low temperature dielectric spectroscopy and high temperature impedance spectroscopy measurements indicated more electroactive regions than anticipated [9,38]. The compositional variables give however even to simple single-phase ceramic materials a complex behaviour, therefore the structural, electrical and relaxor properties of TTBs have to be deeply investigated [10,11,13,21].…”
Section: Introductionmentioning
confidence: 99%
“…The slowing of dipolar response on cooling and the eventual "locking" of the B-cation displacements along the c-axis, (i.e. dipole freezing) was observed [12], while the dynamics of dielectric relaxation of dipoles was extensively investigated by Vogel-Fulcher (VF); the VF fits proved to be very sensitive on the processing parameters [6,36], and the main relaxor behaviour being accompanied by both elastic and anelastic relaxations, as observed by resonance ultrasound spectroscopy (RUS) [37].…”
Section: Introductionmentioning
confidence: 99%